2019
DOI: 10.1002/mus.26437
|View full text |Cite
|
Sign up to set email alerts
|

Decoupled epineurial and axonal deformation in mouse median and ulnar nerves

Abstract: Introduction Peripheral nerves accommodate mechanical loads during joint movement. Hypothesized protective features include increased nerve compliance near joints and axonal undulation. How axons perceive nerve deformation is poorly understood. We tested whether nerves increase local axonal undulation in regions of high epineurial strain to protect nerve fibers from strain‐induced damage. Methods Regional epineurial strain was measured near the elbow in median and ulnar nerves of mice expressing axonal fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…First, the epineurium was excluded from the ROI used to quantify the shear wave velocity. Nevertheless, a recent nerve model suggests a tightly coupled meso-epi-perineurium interacting with a loosely coupled peri-endoneurium (Sung et al, 2019). Therefore, the meso-epineurium connections have the potential to modulate the shear wave velocity of the perineurium, and consequently contribute to the spatial variations observed along the course of the nerve tract.…”
Section: Discussionmentioning
confidence: 99%
“…First, the epineurium was excluded from the ROI used to quantify the shear wave velocity. Nevertheless, a recent nerve model suggests a tightly coupled meso-epi-perineurium interacting with a loosely coupled peri-endoneurium (Sung et al, 2019). Therefore, the meso-epineurium connections have the potential to modulate the shear wave velocity of the perineurium, and consequently contribute to the spatial variations observed along the course of the nerve tract.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with such findings and in line with our results, in a nerve repair experiment Bora et al (9) showed that although there was an initial increase in nerve tension immediately after excising a segment, the nerve returned to its uncut state of tension after seven weeks, with increased compliance within neural connective tissue observed. Additionally, the stiffness adaptations may also be related to changes in neural collagen fibril type and density (39) and in the meso᎑ epi᎑perineurium connections (55). However, such evidence is either indirect or based on studies with animals, whose growth and adaptation patterns differ from humans.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mechanical properties of peripheral nerves are not equal along their length [ 24 ], revealing a complex tissue ultrastructure [ 25 ]. A recent model of nerve layer connections has been proposed to explain the complex (whole) nerve response to stretch [ 26 ]. This model suggests that the mesoneurium, epineurium, and perineurium are coupled via viscoelastic physical connections and interact with a loosely coupled perineurium and endoneurium, allowing axons to glide and unravel throughout the length of the nerve.…”
Section: A Structure Designed To Handle Tensionmentioning
confidence: 99%
“…This model suggests that the mesoneurium, epineurium, and perineurium are coupled via viscoelastic physical connections and interact with a loosely coupled perineurium and endoneurium, allowing axons to glide and unravel throughout the length of the nerve. Collectively, these mechanical features allow nerves to straighten without bearing significant stresses while maintaining functional and structural integrity of the delicate axons within [ 26 ].…”
Section: A Structure Designed To Handle Tensionmentioning
confidence: 99%